Online Teaching Learning during Covid-19 Outbreak: Teacher’s Perception at Junior High School of Fathimatul Amin Jakarta - Minkhatun Nakhriyah; Muhammad Muzakky (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
Pandemic of Covid-19 outbreak has fundamentally replaced the paradigm of education. The teaching learning activity opens up to out of classroom through technology application. Then, this study was aimed to explore the teacher’s perspective to the implementation of online teaching and learning. This research used descriptive qualitative design. Thirty-three teachers were involved in this study. The questionnaire was conducted to investigate the teachers’ perception. Based on the findings, it showed that teachers argued that the teaching media becomes more interactive through many online teaching platforms such as Zoom, Google Meeting, Google classroom, and WhatsApp. Then, teaching via teleconference improve teachers’ skills as well as their confidence because they can present the teaching material and classroom activities creatively. Having said that, teachers face several challenges during online teaching. First, teachers have problem to interact with students due to they tend to be passive during video conference. Then, some students have badly internet connection. Last, the students are lack of learning motivation such as often absence and lately to submit the assignment.